Patients’ Perceptions on Group Cognitive Behavioral Therapy for Obesity - Westphalen, Roberta Bilibio (2023)
Objective. The aim of this study was to analyze the feedback of individuals with obesity diagnosis after 8 Group Cognitive-Behavioral Therapy (GCBT) sessions. Method. 13 patients with previous obesity diagnosis participated. The instrument was an interview conducted at the last meeting of the GCBT; subsequently, a Bardin’s content analysis was carried out. Results. The obtained data was organized into four categories: benefits of participation in the intervention; weight loss and self-esteem; improvement in nutrition quality; and improvement in physical health and life quality. Beyond weight loss, there was an improvement in the quality of nutrition, weight loss, well-being, self-esteem, and, consequently, in the quality of life. Aside from its application in obesity treatment, GCBT can be a promising approach in the treatment of other disorders.